COMPUTER MODELLING OF THERMAL AND AERODYNAMIC CHARACTERISTICS OF COAL HEATSTATION - S.A. Bolegenova (Вестник. Серия физическая, 2010)
In this paper we have described a mathematical model of the process of burning solid fuel in the combustion chamber. The physical model has developed and the technical details BKZ160 camera have described. A study the effect of «Overfire Air Technology» on the results of computational experiments on the modeling of combustion in the combustion chamber was conducted on the basis of the mathematical model.